Dispositional Flow and Performance in Brazilian Triathletes - Garcia, William Fernando; Codonhato, Renan; Mizoguchi, Marcus Vinicius; do Nascimento Junior, José Roberto Andrade; Aizava, Paulo Vitor Suto; Ribas, Marcelen Lopes; Caruzzo, Aryelle Malheiros; Vissoci, João Ricardo Nickenig; Fiorese, Lenamar (Frontiers in Psychology, 2019)
Flow is a mental state characterized by total imersion and focus in an activity, performing it pleasurably, such state is also considered optimal for performance. Present study aimed to analyze the relationship between dispositional flow and performance in triathletes. Sample consisted of 328 athletes (294 males and 34 females; mean age of 37.42±7.18 years) competing in the Ironman Brazil – Florianópolis – South American Championship 2017. Instruments were an identification sheet, the Dispositional Flow Scale (DFS-2) and athletes’ GPS/Garmin data. Data were analyzed using R, through Shapiro-Wilk normality test, Mann-Whitney’s U, Spearman Correlation and Network Analysis (LASSO), using strength, closeness and betweenness as centrality measurements. Results have shown positive correlation between age and total time (r=0.34), inverse relationship between time of practice and total time (r= -0.25), and inverse correlations between total time and 05 of the 09 flow dimensions (r between -0.17 and -0.11); flow conditions, flow characteristics, individual characteristics and performance were separately grouped in the network structure, challenge-skill balance was the most influential node, with the highest closeness and betweenness values; challenge-skill balance, clear goals, control and action-awareness merge directly influenced better race times. Sample’s top 50 performers had significantly higher disposition to challenge-skill balance, clear goals, control and feedback. Flow mechanisms and practical implications are discussed. Dispositional flow was positively related to performance in Brazilian triathletes.